Macronutrient intakes in 553 Dutch elite and sub-elite endurance, team, and strength athletes: Does intake differ between sport disciplines? - Wardenaar, F.; Brinkmans, N.; Ceelen, I.; Van Rooij, B.; Mensink, M.; Witkamp, R.; De Vries, J. (Nutrients, 2017)
Web-based 24-h dietary recalls and questionnaires were obtained from 553 Dutch well-trained athletes. The total energy and macronutrient intake was compared between discipline-categories (endurance, team, and strength) within gender, and dietary inadequacy, i.e., too low or high intakes, according to selected recommendations and guidelines, was evaluated by applying a probability approach. On average, 2.83 days per person were reported with a mean energy intake of 2566-2985 kcal and 1997-2457 kcal per day, for men and women, respectively. Between disciplines, small differences in the mean intake of energy and macronutrients were seen for both men and women. Overall, 80% of the athletes met the suggested lower-limit sport nutrition recommendation of 1.2 g·kg-1 of protein per day. The carbohydrate intake of 50%-80% of athletes was between 3 and 5 g·kg-1 bodyweight, irrespective of the category of their discipline. This can be considered as low to moderate, in view of their daily total exercise load (athletes reported on average ~100 minutes per day). In conclusion, only small differences in the mean energy and macronutrient intake between elite endurance, strength, and team sport athletes, were found. The majority of the athletes were able to meet the generally accepted protein recommendation for athletes, of 1.2 g·kg-1. However, for most athletes, the carbohydrate intake was lower than generally recommended in the existing consensus guidelines on sport nutrition. This suggests that athletes could either optimize their carbohydrate intake, or that average carbohydrate requirements merit a re-evaluation.